PENGARUH BEBERAPA CAMPURAN ECO ENZYME TERHADAP HASIL DAN KUALITAS RUMPUT GANDUM (Triticum aestivum L.) - Cahyo, Kurniawan Dwi; Banjarnahor, Dina (Percetakan Umi Toaha Makassar, 2025)
Wheatgrass is a plant that is harvested less than two weeks after it is planted. Wheatgrass contains higher chlorophyll and carotenoids than adult plants. Spraying eco enzyme, distilled water, and ascorbic acid (EAA) produced the highest average carotenoid content (4.914 mg/g), which was not significantly different from the eco enzyme and distilled water (EA) treatment but was significantly different from the other treatments. The results of this study indicate that the spraying treatment of a mixture of eco enzyme + distilled water + ascorbic acid (EAA) is a good eco enzyme mixture treatment to be further developed for wheatgrass cultivation. This study aims to determine the effect of various eco-enzyme mixtures on the yield and quality of wheatgrass (Triticum aestivum L.). This study used a Simple Completely Randomized Design with four eco enzyme mixture treatments, namely eco enzyme + lemongrass boiled water (ES), eco enzyme + lemongrass boiled water + ascorbic acid (ESA), eco enzyme + distilled water (EA), and eco enzyme + distilled water + ascorbic acid (EA). Each treatment was repeated 2 times and placed in 6 groups. The results of this study showed a significant effect on the carotenoid content variable.